AN ANALYSIS OF REPAYMENT OF AGRICULTURAL CREDIT IN THENI DISTRICT WITH SPECIAL REFERENCE TO BANK OF INDIA - Babu, V.Suresh; Arputharaj, R.; Rajesh, G. (International Journal of Psychosocial Rehabilitation, 2020)
The Bank of India is one of the public sector banks in India. It has started with noble objective of developing rural economy by providing credit facilities. The bank of India has more than 3400 achieved cent percent networking status in all over the India. The developing country like India mainly depends with the agricultural industry. The agricultural industry has played a vital role on rural economy. The bank of India mainly concentrating on rural economy, and it provides agricultural term loans for land development, minor irrigation, farm mechanization, plantation of crops and loan for allied. The present study analyzes the recovery performanceof agricultural loan and problem faced by the respondents in repayment. The study has been conducted in Theni district of Tamilnadu and the study is based on primary data collected through well-structured interview schedule. The results of thestudy have been complied by using average and percentage method.